Photoinitiated synthesis of poly(poly(ethylene glycol) methacrylate-co-diethyl amino ethyl methacrylate) superabsorbent hydrogels for dye adsorption - Alokour, Mamoon; Yilmaz, Elvan (Wiley, 2019)
Random copolymers of poly(ethylene glycol) methacrylate (PEGM), and diethyl amino ethyl methacrylate (DEAEM) were synthesized at low, and high conversions by photoinitiation. Crosslinked poly(PEGM-co-DEAEM) samples were obtained, and characterized by FTIR, SEM, DSC, TGA, and elemental analyses. Swelling behavior of the copolymers revealed that the copolymers acted as superabsorbent hydrogels. The monomer reactivity ratios were calculated using Fineman Ross, Extended Kelen Tudos, and Mayo Lewis methods that gave r(1)(PEGM) = 0.90, r(2)(DEAEM) = 0.14 at low conversions. At high conversions r(1) and r(2) values were calculated as 1.01 and 0.40, respectively. Adsorption isotherms of methyl orange (MO) onto hydrogels were studied using Langmuir, Freundlich, and Temkin models. The experimental data fitted well with the Langmuir equation. The maximum adsorption capacity for MO was 212.7 mg g(-1) at pH = 3. The adsorption data gave best fit with the pseudo-second order kinetic model. Thermodynamic evaluation showed spontaneous nature for MO adsorption onto poly(PEGM-co-DEAEM) hydrogels. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47707.
Keywords: dye adsorption; methacrylate hydrogels; monomer reactivity ratio; photoinitiated copolymerization; superabsorbent